The computer contradictionary - Kelly-Bootle, Stan (MIT Press, 1995)
"New computer cultures and their jargons have burgeoned since this book's progenitor, The Devil's DP Dictionary, was published in 1981. This updated version of Stan Kelly-Bootle's romp through the data processing "laxicon" is a response to the "Unix pandemic" that has swept academia and government, to the endlessly hyped panaceas offered to the MIS, and to the PC explosion that has brought computer terminology to a "hugely bewildered lay audience."" "The original dictionary, an urbane and witty pastiche of Ambrose Bierce's famous work, parried chiefly the mainframe and mini-folklore of the 1950s, 1960s, and 1970s. This long awaited revision adds over 550 new entries and enhances many of the original definitions. Key targets are "a host of new follies crying out for cynical lexicography [including] the GUI-Phooey iconoclasts, object orienteering, and the piping of BLObs down the Clinton-Gore InfoPike.""--Jacket